Where to draw the line: the difference between a fan and a pirate in Japan. Issue 4 (6th June 2020) - Schroff, Simone
ABSTRACT: This article examines the gap between the public discourse favoured by right holders and politicians for strict copyright enforcement and industry practice where infringement is tolerated and sometimes even facilitated by the same right holders. Drawing on the Japanese contents sector surrounding Manga, Anime and video games, the interaction between strict copyright provisions, positive and negative market impact and broader considerations such as reputation and pay-offs are contextualised. It is demonstrated that right holders do not see infringing behaviour as such as a cause of action nor does it dominate how right holders want users to interact with their products. Instead, it is the wider context which determines if copyright will be enforced or not. Based on an analysis of copyright law, stakeholder interviews and observations at industry and stakeholder events, this paper clarifies where right holders draw the line between a pirate and a fan, especially the limited influence copyright law has in practice.